PENGARUH HUMAN RELATION, LINGKUNGAN KERJA, PELATIHAN DAN PENGEMBANGAN SDI TERHADAP ETOS KERJA KARYAWAN SERAMBI INDONESIA - Presilawati, Febyolla; Pratama, Rangga Firta (JSI: Jurnal Saudagar Indonesia, 2025)
A company is able to achieve its goals if all employees can provide maximum results based on work ethic within the employees, then the employees will work more effectively and more satisfactorily. This study intends to measure and recognize the influence of Human Relations, physical conditions of the work environment, training, employee development on work ethic in the Serambi Indonesia office. The population and sample are all employees totaling 50 people. The results of the analysis show that Human Relations does not have an effect on work ethic in the Serambi Indonesia office, while the physical conditions of the work environment, job training, employee development have a positive effect on work ethic in the Serambi Indonesia office. While the results of R2 are 67.4%, meaning that all variables play a major role in work ethic